Review paperOn the ‘classification’ of neurodegenerative disorders: discrete entities, overlap or continuum? - A. Armstrong, Richard (Folia Neuropathologica, 2012)
The traditional method of classifying neurodegenerative diseases is based on the original clinico-pathological concept supported by ‘consensus’ criteria and data from molecular pathological studies. This review discusses first, current problems in classification resulting from the coexistence of different classificatory schemes, the presence of disease heterogeneity and multiple pathologies, the use of ‘signature’ brain lesions in diagnosis, and the existence of pathological processes common to different diseases. Second, three models of neurodegenerative disease are proposed: (1) that distinct diseases exist (‘discrete’ model), (2) that relatively distinct diseases exist but exhibit overlapping features (‘overlap’ model), and (3) that distinct diseases do not exist and neurodegenerative disease is a ‘continuum’ in which there is continuous variation in clinical/pathological features from one case to another (‘continuum’ model). Third, to distinguish between models, the distribution of the most important molecular ‘signature’ lesions across the different diseases is reviewed. Such lesions often have poor ‘fidelity’, i.e., they are not unique to individual disorders but are distributed across many diseases consistent with the overlap or continuum models. Fourth, the question of whether the current classificatory system should be rejected is considered and three alternatives are proposed, viz., objective classification, classification for convenience (a ‘dissection’), or analysis as a continuum.